myCMIE: My cancer molecular information exchange - Xu, Qi; Kowalski, Jeanne (iScience, 2023)
Molecular profiling reports (MPRs) are critical for determining treatment options for cancer patients. They include several pages of information on genomic findings, drugs, and trial options that are challenging to synthesize for effectively and expeditiously informing on treatment. Xu and Kowalski present a web application, myCMIE, that synthesizes MPR content to define a patient-centric, information system in which molecular profiles are exchanged between a query case(s) and public resources or user-input case series for context-informed treatment and conjecture with therapeutic implication. myCMIE offers an interactive build of coordinately connected digital-twin communities to expand our understanding of treatment context with multiple visuals to stimulate discussions among diverse stakeholders in care. [Display omitted] •myCMIE builds a patient-centric, coordinate molecular information exchange system•myCMIE leverages known with unknown variants to define a total molecular profile•A web-based application for interactive analyses of molecular profile content•A multi-visual presentation of results for multi-stakeholder understanding Health informatics; Biomolecules; Molecular physiology; Cancer